2007
DOI: 10.1002/j.2055-2335.2007.tb00752.x
|View full text |Cite
|
Sign up to set email alerts
|

SHPA Standards of Practice for the Provision of Medication Reconciliation

Abstract: These are standards of professional practice and not standards prepared or endorsed by Standards Australia. They are not legally binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…6 The practicality of this goal is far from realistic as it relies on having a fully staffed pharmacy department. It is imperative to highlight that these standards describe a 'best practice' model of service.…”
Section: Economic Evaluation -A Tool To Support Hospital Formulary Asmentioning
confidence: 99%
“…6 The practicality of this goal is far from realistic as it relies on having a fully staffed pharmacy department. It is imperative to highlight that these standards describe a 'best practice' model of service.…”
Section: Economic Evaluation -A Tool To Support Hospital Formulary Asmentioning
confidence: 99%
“…230,231 To ensure that a complete and accurate list of medicines is taken prior to presentation to hospital, confirmation with a second source is recommended. 230,232 When this was discussed with those responsible, it was found that this procedure had been followed (confirmation with two sources), but not documented. 233 This puts documentation as an area to target.…”
Section: Medication Historiesmentioning
confidence: 99%
“…Medication reconciliation ensures that the patient receives all intended medicines and reduces common errors of transcription, omission, duplication, medicinemedicine and medicine-disease interactions. 80,230,232,234 Medication reconciliation is a process that needs to be documented within our service and is done by the pharmacist when a patient is reviewed. There is currently a clinical pharmacist based on the ward who is able to perform reconciliation.…”
Section: Medication Historiesmentioning
confidence: 99%
See 2 more Smart Citations